Increased microvascular flow and foot sensation with mild continuous external compression - Rosales‐Velderrain, Armando (Wiley Periodicals, Inc., 2013)
Intermittent pneumatic compression of the calf and foot increases inflow to the popliteal artery and skin. We hypothesize that mild, continuous pneumatic compression of the lower extremities of type 2 diabetic patients increases microvascular blood flow to skin (SBF) and muscle (MBF) and improves sensation in feet. Data were collected on 19 healthy volunteers and 16 type 2 diabetic patients. Baseline values of SBF, MBF, and foot sensation were recorded in one leg. The lower extremity was then subjected to 30 mmHg of continuous external air pressure for 30 min, whereas SBF and MBF were continuously monitored. Sensation was reassessed after pressure was released. During 30 mmHg continuous external compression, the healthy control group significantly increased MBF by 39.8% (P < 0.01). Sensation of the foot in this group improved significantly by 49.8% (P < 0.01). In the diabetic group, there was a significant increase in MBF of 17.7% (P = 0.03). Also sensation improved statistically by 40.2% (P = 0.03). Importantly and counterintuitively, MBF and foot sensation both increase after 30 min of leg compression at 30 mmHg. Therefore, mild, continuous pneumatic compression may be a new approach for treating diabetic patients with compromised leg perfusion and sensation.